Competencies Needed by Agricultural Communication Undergraduates: A Focus Group Study of Alumni - A. Christian Morgan (Journal of Applied Communications, 2012)
A focus group study was conducted with agricultural communication program alumni to determine the competencies needed in current graduates of the University of Georgia program. Of the 12 alumni invited to contribute, four participated in the study, which represented a breadth from a recent graduate to a seasoned vice president in a global advertising agency. The competency receiving the greatest level of importance was the ability to write well; other competencies included having a familiarity with all types and styles of writing, in particular magazine or feature style. Possessing a broad spectrum of communication skills was also important, including public speaking, audience identification, conveying written thoughts well, using proper style, identifying a story, and strategic writing. In addition, understanding how new media is changing the industry and how to use that media effectively was expressed. Although agricultural knowledge and skills are a large part of the degree, participants stressed communication skills are the foundation. General employment skills, in the form of a good work ethic and willingness to take on basic tasks, were also emphasized. Recommendations included conducting research to determine faculty perspectives of competencies needed by program graduates, which forms of new media should be taught in programs, and what agricultural knowledge is most important for graduates to possess.
Keywords: Curriculum; focus group; undergraduate; alumni